(untitled) (Heteroglossia – studia kulturoznawczo-filologiczne, 2022)
The article deals with J.R. Skoyles’s theory of right hemisphere literacy which challenges the paradigm of left hemisphere dominance in the reading process and claims that in the early textual cultures the right hemisphere may have played a dominant role in reading. Applying this theory to Arab-Muslim culture, one would claim that in the early stages of the development of Arabic writing, reading may have been right-hemispheric in nature. The activity of the right hemisphere was related to the direction of writing leftwards. Moreover, Arabic script, whose reading is contextual due to the lack of short vowels, may have involved the right hemisphere to a relatively large extent in its processing and may have fostered the ‘preservation’ of its involvement even after the development of left hemisphere literacy. Finally, the presence of connections between letters in an Arabic word could also stimulate the participation of the right hemisphere in reading. At the same time, the development of left hemisphere literacy, now dominant among native Arab right-handed readers, did not necessarily have to be linked to a change in the direction of writing due to its high status in the culture linking it to the God and His word.